Remote platelet function testing using P-selectin expression in patients with recent cerebral ischaemia on clopidogrel. Issue 1 (24th September 2020) - Appleton, Jason Philip; Richardson, Carla; Dovlatova, Natalia; May, Jane; Sprigg, Nikola; Heptinstall, Stan; Bath, Philip M
Abstract : Background: Antiplatelet agents reduce recurrence after cerebral ischaemia but are not effective in all patients, in part because of treatment resistance. The primary aim was to assess the proportion of patients who are insensitive to clopidogrel. The secondary aim was to assess the association between insensitivity to clopidogrel and recurrent cerebrovascular events. Methods: Following written informed consent, independent patients with a recent non-cardioembolic ischaemic stroke or transient ischaemic attack, and taking clopidogrel, were enrolled. Platelet function was assessed with remote measurement of surface expression of P-selectin (CD62P) using commercial kits sensitive to aspirin or clopidogrel. Participants' general practitioners provided details on recurrent vascular events at least 90 days later. Data are mean (SD) and median [IQR]. Resistance was defined as: aspirin median fluorescence (MF) >500 units, clopidogrel MF >860 units. Non-parametric descriptors and tests were used. Results: 63 patients were recruited: mean age 64 (13.7) years, women 47%. At baseline, 59 (95%) patients were taking clopidogrel alone with 3 (5%) on combined clopidogrel and aspirin. Assessment of platelet surface P-selectin revealed: aspirin test 528 [317, 834], >500 54.8%; clopidogrel test 429 [303, 656], >860 11.3%. No participants on aspirin and clopidogrel showed aspirin resistance. Thirteen (20.6%) patients had a recurrent cerebrovascular event; those with an ischaemic stroke had a non-significantly higher baseline P-selectin using the clopidogrel test as compared with those with no recurrence: 626 [380, 801] versus 406 [265, 609], p=0.08. Conclusions: Remote measurement of platelet function assessed using the platelet surface expression of P-selectin is feasible. 11% of patients taking clopidogrel showed resistance. No significant associations were noted between clopidogrel resistance and recurrent ischaemic events.